Preparation of Phthalimide and Kinetics of Vapour Phase Ammoxidation of o-Xylene on V-Sb-Bi-Cr/g-Al2O3 Oxide Catalyst-III - Bagirzade, G.A.; Tagiyev, D.B.; Guliyev, F.A.; Manafov, M.R. (Asian Journal of Chemistry, 2017)
The conditions for the synthesis of phthalimide by vapour phase ammoxidation of o-xylene on V-Sb-Bi-Cr/g-Al2O3-oxide catalyst were studied. The optimum process conditions to obtain the phthalimide as the main reaction product were determined. It is shown that the problem of difficult separation of crystal mixture of main products in the synthesis of phthalimide, solved with full conversion of o-xylene in a single process, using low concentrations of ammonia and water in the initial reaction mixture, which differs from the phthalonitrile obtaining an average from the substrate conversion to oxide catalyst V-Sb-Bi-Zr/g-Al2O3 by recirculation at high concentrations of ammonia.